Sectoral Analysis of the Participation of the Public and Private Agents in the Production Activities in Egypt. An Efficiency Perspective - Helmy, Ashraf (The Arab Journal of Administration, 2025)
This study aims at examining the efficiency of the participation of the public and private agents in the production process in different productive sectors of the Egyptian economy during the period 2003-2018. The study utilized the Stochastic Frontier Analysis (SFA), also known as the Composed Error model, to determine the efficiency of a production function that consists of labor and capital, as inputs, and the generated value-added by the two productive economic agents, as outputs. The study found differentiated results across the productive sectors regarding the relative weights of the public and private agents and the efficiency of their technical performance, on the one hand, and the returns and contributions of labor and capital factors by the two economic agents in the productive sectors, on the other hand. The relative weak contribution of the public agents in the agriculture sector is commensurate with the low efficiency of their technical performance, and the sector is dominated by the private agents, which are relatively technically more efficient. Despite the technical performance of the private and public agents is almost equivalent in both the mining and manufacturing sectors; however, the public agents dominate the mining sector, while the private agents dominate the manufacturing sector. Regarding the services sector, the private agents perform with a relatively high level of technical efficiency and dominate the sector. In general, the study found that the relative weights of the public and private agents in different productive sectors in Egypt are, to a large extent, commensurate with their level of technical efficiency.